Primary peritoneal drainage in critically ill patients of perforation peritonitis (an experience of 60 cases) - Bhasin, Sanjay Kumar; Sharma, Vivek; Azad, Tariq Parveez (International Surgery Journal, 2017)
Background: Objective of the present study was to evaluate applicability of Primary Peritoneal Drainage (PPD) under LA in critically ill patients as pre-laparotomy support when laparotomy under GA could not be done. Also to assess outcome in terms of survival, patients needing definitive surgery and complications associated with the procedure on immediate and follow up basis. Methods: A prospective designed study including 60 critically ill patients admitted and diagnosed as perforation peritonitis were subjected to PPD under LA as per inclusion and exclusion criteria, at GMC Jammu, Jammu and Kashmir, India from November 2013 to October 2015. Results: The average age of patients was 53.43 years (20-80 years) with M:F ration of 7:3. All patients presented in shock with very high ASA, combined and MPI scores. 40 patients died after PPD/laparotomy and 20 patients survived. From amongst survivors, 08 (40%) patients required no further treatment and 12 (60%) survivors required definitive laparotomy and treatment of the cause. Overall mortality was 66.67%, attributed to extraordinary delay in presentation, old age, High ASA and other score. Conclusions: From the present study it was concluded that in adults the procedure did not proved comparable to standard surgical intervention as definite procedure but it did proved to be an effective modality of resuscitation and patient stabilization unlike in NEC of infants; PPD under LA. Overall the procedure is a low cost intervention and provide cheaper alternative to sustain and improvise the status of patient with a possibility of widespread applicability in low resource situations provided interdepartmental support from ICU, Dialysis and CCU is available.